What is an Editorial and How to Write? - Mahendra Singh Ashawat; Sanaul Mustafa; Vinay Pandit (German Journal of Pharmaceuticals and Biomaterials, 2024)
Either the editor or someone else who has been invited by the editor may write an editorial. On top of that, it serves a multitude of other purposes, such as providing critiques of original articles that were published in the same issue of the journal, providing brief reviews of subjects that do not warrant a fulllength invited review, and providing other topics on very recent developments that the editor believes are important to the readers of the journal and the community. Because the editorial often has a limited amount of space in which to present its contents, the message that is contained within it needs to be carefully thought out and given in a concise manner. A clear conclusion should be included at the end of the section, and it should have the correct sequencing of the elements of critical argument. Ideally, it should be supported by evidence.